Risk Classification for Enteroviral Infection in Children With Meningitis and Negative Gram Stain. Issue 11 (November 2018) - Zakhour, Ramia; Aguilera, Elizabeth; Hasbun, Rodrigo; Wootton, Susan H.
Abstract : Objectives: Enterovirus is the most common cause of aseptic meningitis in children. This study aimed at identifying baseline variables associated with a positive cerebrospinal fluid (CSF) Enterovirus polymerase chain reaction (PCR) to aid clinicians in targeting patients who could be tested and treated as outpatients. Methods: We performed a retrospective review of children (2 months to 17 years old) admitted to the Children's Memorial Hermann Hospital in Houston, TX, between January 2005 and December 2010 with symptoms of meningitis, CSF white cell count of greater than 5 cells/mm 3, and a negative CSF Gram stain, who had a CSF Enterovirus PCR. Results: One hundred thirty-seven children were reviewed; median age was 4.7 (0.1–17.1) years, and 79 (58%) were male. Fifty patients (37%) had positive CSF Enterovirus PCR. Only 13 (15%) of the Enterovirus PCR-negative patients had an identifiable etiology. All patients were hospitalized. The mean hospital stay for patients with Enterovirus was 2.9 days; 88% received empiric antibiotics. Rates of antibiotic administration were not different between PCR-positive and PCR-negative groups ( P > 0.05). All patients with Enterovirus had a favorable clinical outcome. A predictive model was created using 3 baseline variables independently associated with a positive Enterovirus PCR ( P < 0.05): May to November presentation, CSF protein of less than 100 mg/dL, and absence of focal neurologic signs. The model classified patients into 2 risk categories for a positive Enterovirus PCR (low risk, 0% [0/17 patients]; high risk, 42% [50/120 patients]; P < 0.001). Conclusions: Our predictive model can be used to identify children for whom Enterovirus PCR testing is warranted. Such testing could avoid unnecessary hospitalization and antibiotic administration.